Unlocking Growth: Exploring How Social Capital, Organizational Learning Capability Shape Business Performance through Business Model Innovation - Heri Setiawan; Abd Jalaludin Sayuti (Universitas Negeri Malang, 2024)
This study focuses on revealing the power of social capital and organizational learning capabilities to increase business performance by using business model innovation as a mediation variable. The population of this study was micro and small enterprises in Palembang amounting to 1.103 SMEs and the sample used was 172 SMEs. The sampling technique uses purposive sampling assuming micro and small enterprises are still actively running their businesses until Agustus 2023. Data analysis uses an SEM-based structural model approach. The survey findings revealed that social capital could significantly improve business model innovation but not for business performance. Organizational learning capabilities could significantly improve business model innovation and performance. Then, business model innovation can reinforce social capital ties, organizational learning capabilities, and business performance. This survey expands the existing knowledge by scrutinizing the role of business model innovation as mediation between social capital and organizational learning capabilities, and, hence, makes a notable adjunct to the existing knowledge in the micro and small enterprises context by concentrating on the connection between social capital, organizational learning capability, business model innovation, and business performance. Keywords: Business model innovation, Business performance, Organizational learning capabilities, Social capital, SMEs